Wettability of Thin Silicate-Containing Hydroxyapatite Films Formed by RF-Magnetron Sputtering - Gorodzha S. N. Svetlana Nikolaevna; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Gribennikov M. V.; Pichugin V. F. Vladimir Fyodorovich; Sharonova A. A. Anna Aleksandrovna; Pustovalova A. A. Alla Aleksandrovna; Prymack O.; Epple M.; Wittmar A.; Ulbricht M.; Gogolinskii K. V.; et al. (2014, 2014)
Title screen